2020
DOI: 10.1002/ente.202000092
|View full text |Cite
|
Sign up to set email alerts
|

Photovoltaic Performance of Porphyrin‐Based Dye‐Sensitized Solar Cells with Binary Ionic Liquid Electrolytes

Abstract: Herein, green porphyrin sensitizer Y350‐based dye‐sensitized solar cells (DSCs) with binary ionic liquid–based electrolytes are studied, which are a mixture of 1‐methyl‐3‐propyl‐imidazolium iodide and 1‐methyl‐1‐butylpyrrolidinium bis(trifluromethylsulfonyl) ‐imide, 1‐butylpyridinium bis(trifluromethylsulfonyl)imide, 1‐methyl‐3‐ethylimidazolium bis(trifluromethylsulfonyl)imide, or 1‐methyl‐3‐ethylimidazolium tetracyanoborate. The best semitransparent green DSC device exhibits a short‐circuit photocurrent densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…This study determined that this redox system rapidly regenerated indoline dyes within the range of tens of nanoseconds, several orders of magnitude faster than cobalt(II/III) shuttle [Co(bp y) 3 ] 2+/3+ [NTf 2 ] 3/2 [225]. As a result of the volatility of the organic solvent employed in electrolyte solutions, some groups have expanded investigations into non-volatile routes for DSSC fabrication [212,226,227]. Cao and coworkers have developed a solid-state DSSC (ssDSSC) based on [Cu(tmby) 2 ] +/2+ [NTf 2 ] 2 redox shuttle for a hole transport layer [228].…”
Section: Recent Advances In Dye-sensitized Solar Cellsmentioning
confidence: 99%
“…This study determined that this redox system rapidly regenerated indoline dyes within the range of tens of nanoseconds, several orders of magnitude faster than cobalt(II/III) shuttle [Co(bp y) 3 ] 2+/3+ [NTf 2 ] 3/2 [225]. As a result of the volatility of the organic solvent employed in electrolyte solutions, some groups have expanded investigations into non-volatile routes for DSSC fabrication [212,226,227]. Cao and coworkers have developed a solid-state DSSC (ssDSSC) based on [Cu(tmby) 2 ] +/2+ [NTf 2 ] 2 redox shuttle for a hole transport layer [228].…”
Section: Recent Advances In Dye-sensitized Solar Cellsmentioning
confidence: 99%
“…Imidazolium-based ionic liquids have been widely used as electrolyte components for lithium-ion batteries, [18,19] DSSCs, [20,21] supercapacitors [22,23] and field effect transistors [24,25] due to their low viscosity, [26,27] high conductivity, [28,29] non-flammability [30] and ease of functionalization through the available 1,3-positions. Regarding the conductivity of the ILs, it has been reported that oxygen atoms on the side chains of cation provide relatively higher conductivity values compared to the ones with the same length of n-alkyl chains due to ion-ion and van der Waals interactions.…”
Section: Introductionmentioning
confidence: 99%
“…MPII is normally combined with lower viscosity and non‐redox ILs to reduce its high viscosity. This is because the viscosity of the binary ILs electrolyte is determined by the viscosity of non‐redox IL added in MPII 14 . In general, the viscosity of ILs has been found to have the greatest impact on the efficiency of DSSCs.…”
Section: Introductionmentioning
confidence: 99%